A concept for construction new currency baskets based on statistical criteria - Duda, J. T.; Mazur, M. (Видавництво Національного університету "Львівська політехніка", 2009)
Two approaches to construction new currency baskets are proposed. The first one is based on the Karhunen-Loeve transformation (PCA) of time series of more important currencies exchange rates, and employs the least variance component of the transformed series as the most stable currency. The second one uses formal optimization techniques to find a currency basket minimizing variability of prices of representative raw materials (non-iron metals and fuels).